Influence of Aggregate Gradation and Pore Structure on Porous Asphalt Mixture Permeability and Resilient Modulus - Gummadi Chiranjeevi; S Shankar (Journal of Rehabilitation in Civil Engineering)
A porous asphalt mixture (PAM) is distinguished by its different porous structures, which allow water to move through it as quickly as possible, making drainage an essential component. Porous asphalt pavement (PAP) can maintain its permeability because the mixture contains voids that are interconnected with one another. Permeability, on the other hand, decreases as the proportion of particles in the gradation and the level of compaction increases. To generate various air-void structures, permeability was evaluated with specimens made from varying sizes and shapes of aggregates. The equipment that was used for this research was specifically designed. When compared directly with permeability, the findings indicate that the combination of multiple forms is not directly comparable. The permeability of PAM was observed to be affected by a variety of air void densities, which were observed. While there was a beneficial influence on permeability, there was a negative impact on the Resilient Modulus (MR), which was detected when there was an increase in the void content. The amount of air voids in the mixture substantially impacts the performance of porous asphalt mixtures. Open-Gr-I viscosity grade (VG30) bitumen has a permeability value of 0.394 cm/s, and the resilience modulus value for open-Gr-II mixtures that use a modified binder is 3494 MPa. Both of these values are relative to the permeability value. The drainage and stiffness metrics for the several combinations investigated in this study were considerably impacted by the gradation, the kind of binder, and the temperature conditions. Stormwater management is possible in PAP and improves the groundwater table.